Predicate Argument Structure in Haitian Creole - Massam, Diane (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1989)
AbstractThis paper outlines the argument properties of Haitian Creole verbs, including intransitive, transitive, and ditransitive verbs, within a lexical framework which includes a level of Lexical Conceptual Structure and a level of Predicate Argument Structure. There is assumed to be a relatively free mapping relation between these two levels in order to explain the many possible variations in argument structure that most verbs exhibit. We see that there are at least two detransitivizing operations in Haitian Creole: one which operates freely and one which must be adverb-licensed. Transitive and ditransitive verbs are classified in terms of which of these operations they may undergo. The paper presents a description of Haitian Creole verb-types in Government and Binding theoretical terms and highlights several problems which Haitian Creole poses for future research.